Circadian Rhythms, Sleep and Cognitive Skills: Evidence from an Unsleeping Giant - Osea Giuntella; Wei Han; Fabrizio Mazzonna (Institute for the Study of Labor (IZA), 2016)
This paper analyzes the effects of sleep duration on cognitive skills and depression symptoms of older workers in China. Cognitive skills and mental health have been associated with sleep duration and are known to be strongly related to economic behavior and performance. However, causal evidence is lacking and little is known about sleep deprivation in developing countries. We exploit the relationship between circadian rhythms and bedtime to identify the effects of sleep using sunset time as an instrument. Using the Chinese Health and Retirement Longitudinal Study, we show that a later sunset time reduces significantly sleep duration and that sleep duration increases cognitive skills and eases depression symptoms of workers aged over 45 years. The results are driven by employed individuals living in urban areas, who are more likely to be constrained by rigid working schedules. On the contrary, we find no evidence of significant effects on self-employed and farmers.
Keywords: I12; 330; sleep deprivation; cognitive skills; risky behaviors